(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this paper we analyze the polemical disputes about the annulment of the “Due Obedience” and “Full Stop” laws in Argentina and the Law on the Expiration of the Punitive Claims of the State in Uruguay, laws that prevented the pro- secution of those responsible for crimes against humanity during the military dictatorships and that, through different mechanisms, were cancelled in 2003 and 2011 respectively. Both situations can be studied as “litigious memory sce- nes”, i.e. discursive spaces where political litigation is held, and where issues involved in the definition of the political community itself are therefore treated.The main goal of this paper is to reconstruct and compare the main argumenta- tive quaestiones or controversies, and the different positions deployed in each of the scenes analyzed, with emphasis on official discourses.